2020
DOI: 10.1021/acs.jafc.9b06801
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Lipemia Modulates Pancreatic Alpha-Cell Function in the Prediction of Type 2 Diabetes Development: The CORDIOPREV Study

Abstract: Diabetes (T2DM) is a major global health issue, and developing new approaches to its prevention is of paramount importance. We hypothesized that abnormalities in lipid metabolism are involved in alpha-cell deregulation. We therefore studied the metabolic factors underlying alpha-cell dysfunction in T2DM progression after a dietary intervention (Mediterranean and low-fat). Additionally, we evaluated whether postprandial glucagon levels may be considered as a predictive factor of T2DM in cardiovascular patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previous studies have found that T2DM is associated with abnormalities in lipid metabolism such as high fasting and postprandial blood levels of TG, high concentrations of nonesterified fatty acids, and low HDL concentrations [ 9 ]. In addition, a study has reported that hyperlipidemia can increase glucagon in patients with T2DM [ 10 ]. However, the relationship between blood lipid levels and the function of pancreatic α and β cells has been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that T2DM is associated with abnormalities in lipid metabolism such as high fasting and postprandial blood levels of TG, high concentrations of nonesterified fatty acids, and low HDL concentrations [ 9 ]. In addition, a study has reported that hyperlipidemia can increase glucagon in patients with T2DM [ 10 ]. However, the relationship between blood lipid levels and the function of pancreatic α and β cells has been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, accurately reflecting the problems of lipid metabolism by measuring fasting blood lipids alone is difficult. With the increasing emphasis on postprandial lipids, postprandial dyslipidemia is also considered to be an independent risk factor for type 2 diabetes mellitus and atherosclerotic disease 8 , 24 , 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial lipid concentrations are superior to fasting lipids for the prediction of cardiovascular diseases. Furthermore, high postprandial lipid concentrations, especially postprandial TG (PTG) concentrations, might induce α‐cell dysfunction in individuals with cardiovascular disease 8 , leading to a rapid decrease in insulin sensitivity 9 , and thus the development of type 2 diabetes mellitus 10 . Nevertheless, the methods and criteria used to assess postprandial lipids have not been standardized.…”
Section: Introductionmentioning
confidence: 99%
“…The modern diet consists of three to five feeding times a day, and individuals spend a significant amount of time in a non-fasting and postprandial state, meaning the levels of CM, VLDL, and other TRLs and their remnants are enhanced, which leads a continually fluctuating level of blood lipid ( 15 ). The postprandial metabolic status can be better reflected by postprandial TG concentration, and with the combination of fasting TG concentration, the degree of exposure of total TG in the arterial wall within 24 h can be described more comprehensively and accurately ( 16 ). TG reflects the burden of remnant cholesterol (RC) and can be used as its marker.…”
Section: Postprandial Lipemia and Postprandial Hyperlipidemiamentioning
confidence: 99%